Advanced Groundwater Quality Assessment Using Geochemical Analysis and Water Quality Indices with Fuzzy Logic - Seraiche, Lakhdar; Ghodbane, Messaoud; Selmane, Tahar; Dougha, Mostafa (Journal of Engineering and Sustainable Development, 2025)
Groundwater resources in the semi-arid region south of Chott Hodna (Algeria) are increasingly threatened by depletion and salinization, threatening both human consumption and agriculture. This study assessed groundwater quality by analyzing the physicochemical parameters of 45 well samples. It used arithmetic, entropy-weighted, and fuzzy logic-based water quality indices (WQI, EWQI, and FWQI), integrated with GIS-based spatial analysis, to address data uncertainties and variability. The results revealed WQI values ranging from 59.51 to 233.68, with 64.44% of the wells classified as having poor quality due to high concentrations of sulfate, chloride, calcium, and nitrate. EWQI and FWQI showed consistent contamination patterns, with FWQI demonstrating greater accuracy by reducing extreme classifications. Spatial analysis highlighted poor water quality in the Maadher agricultural area, while better quality was observed at the eastern and western ends. Challenges included managing data variability, managing complex methodologies, and ensuring reliable spatial interpolation. The ordinary kriging technique with a spherical semivariogram model effectively identified key pollutants, including nitrate (NO₃⁻), chloride (Cl⁻), and electrical conductivity (EC), concentrated near wadis and agricultural areas.